A novel variable neighborhood descent algorithm for service restoration in radial electrical distribution networks - Puerta, Gabriel F. [UNESP]; Macedo, Leonardo H. [UNESP]; Soares, Joao; Romero, Ruben [UNESP] (Oxford Univ Press, 2024)
This paper presents a variable neighborhood descent algorithm for the service restoration problem (SRP) in electrical distribution systems. The restoration problem appears when a permanent fault occurs in the system. The fault must be localized and isolated from the rest of the system. As a consequence of the isolation, the downstream area is de-energized and requires restoration. The variable neighborhood descent algorithm features its ability to solve the SRP for radial distribution systems and introduces a strategy that helps to deal with the system's radiality. Tests are performed using a 53-node test system. The results show that the proposed algorithm can efficiently solve the SRP in a distribution system, and as a deterministic algorithm, the results can be used to help nondeterministic algorithms.
Keywords: electrical distribution systems; metaheuristic; service restoration; variable neighborhood search